Transverse discrete breathers in unstrained graphene; The European Physical Journal B; Vol. 90, iss. 3 - Barani E.; Lobzenko I. P.; Korznikova E. A. Elena Aleksandrovna; Soboleva E. G. Elvira Gomerovna; Dmitriev S. V.; Zhou K. Kui; Marjaneh A. M. (2017, 2017)
Title screen